Soil-plant nutrient interactions in two mangrove areas at Southern Brazil (2016)
Mangrove forests have a simple architecture. They shelter a few number of arboreal species that grow in a saline environment subject to tidal activity. The research objective was to evaluate possible interactions between physical-chemical soil attributes and plant-leaf nutrient concentrations of different mangrove species. Different mangrove species growing in the same soil, and the same mangrove species growing in two different soil classes were evaluated as to their leaf nutrient concentration patterns. The study was carried out in mangrove areas of the State of Paraná, southern Brazil, in two distinct soil classes: HISTOSOL THIOMORPHIC Salic sodic and GLEYSOL THIOMORPHIC Salic sodic; and three different species: Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle. Two subareas were delimited within each area from which soil and leaf samples were collected. Samplings from five individuals of each dominant mangrove species were taken from the soil (0-10 cm deep) under each tree crown projection. The data was submitted to statistical analysis using a set of simple and multivariate analysis in order to determine possible differences among mangrove species leaf nutrient concentrations, and whether these differences might be correlated with the soil attributes or not.The results exposed that the nutritional state of the mangrove species is different and independent form the soil attributes in which they grow. Few correlations were found among leaf nutrient concentrations and soil attributes, suggesting differential selective nutrient uptake among species.